Enhancement of body performance and growth performance of juvenile mahseer (Tor soro) using differently colored containers - Teuku Fadlon Haser; Eddy Supriyono; Kukuh Nirmala; Widanarni; Tri Heru Prihadi; Tatag Budiardi; Reza Syamsudin; Muh Saleh Nurdin (Fisheries and Aquatic Sciences, 2024)
Mahseer (Tor soro) growth performance tends to be slow, necessitating further development and intensification of cultivation. One way to develop aquaculture intensification is to manipulate cultivation containers to create optimal environmental conditions for the mahseer to grow. This study aimed to examine the body performance and growth performance of mahseer reared in different colored containers. Experimental research with completely randomized design was employed, with four colored container treatments namely treatment A (transparent), B (green), C (blue), and D (black), with four replications in each treatment. Findings indicate that different rearing media colors had significant effect on absolute length (4.68 ± 0.24 cm), absolute weight (1.58 ± 0.35 g), specific growth rate (2.17 ± 0.38%), feed conversion ratio (2.87 ± 0.04), survival rate (100 ± 0.00%), gross energy (3,816 ± 65.05 cal/g), and body proximate. Physiologically, mahseer fish bred using blue and black containers tend to be more resistant to stress.The best body performance and growth performance were observed in the blue and black colored containers.